The tale of Samuel Whiskers, or, The roly-poly pudding - Potter, Beatrix, 1866-1943. ((New York) : Warne, 1987)
Tom Kitten hides from his mother and is caught by rats who want to make him into a kitten dumpling.
Wilson's Children.
3.7
K-3
Keywords: Animals -- Fiction; Animals -- Fiction; Animals -- Fiction; Cats -- Fiction; Rats -- Fiction